Revealing the Relational Mechanisms of Research for Development Throug h Social Network Analysis - Apgar, Marina; Fournie, Guillaume; Haesler, Barbara; Higdon, Grace Lyn; Kenny, Leah; Oppel, Annalena; Pauls, Evelyn; Smith, Matthew; Snijder, Mieke; Vink, Daan; Hossain, Mazeda (The European Journal of Development Research, 2023)
Achieving impact through research for development programmes (R4D) req uires engagement with diverse stakeholders across the research, develo pment and policy divides. Understanding how such programmes support th e emergence of outcomes, therefore, requires a focus on the relational aspects of engagement and collaboration. Increasingly, evaluation of large research collaborations is employing social network analysis (SN A), making use of its relational view of causation. In this paper, we use three applications of SNA within similar large R4D programmes, thr ough our work within evaluation of three Interidsiplinary Hubs of the Global Challenges Research Fund, to explore its potential as an evalua tion method. Our comparative analysis shows that SNA can uncover the s tructural dimensions of interactions within R4D programmes and enable learning about how networks evolve through time. We reflect on common challenges across the cases including navigating different forms of bi as that result from incomplete network data, multiple interpretations across scales, and the challenges of making causal inference and relat ed ethical dilemmas. We conclude with lessons on the methodological an d operational dimensions of using SNA within monitoring, evaluation an d learning (MEL) systems that aim to support both learning and account ability.